Risperidone-induced bruise-like rash in a child - Ekinci, Ozalp (Ann Saudi Med, 2020)
Adverse cutaneous reactions are rarely seen with antipsychotics. Exanthematous eruptions, skin pigmentation changes, photosensitivity, urticaria, and pruritus have been previously reported. We report a bruise-like rash in a 4-year-old boy with risperidone use. The rash disappeared on discontinuation and then reappeared after re-initiating the medication. Clinicians should be aware of a bruise-like skin rash as a rare adverse effect of risperidone. This is especially important for pediatric cases where physical abuse may be suspected. SIMILAR CASES PUBLISHED: None.